PERLINDUNGAN HUKUM BAGI PEMEGANG SAHAM MINORITAS DALAM PENGAMBILAN KEPUTUSAN RAPAT UMUM PEMEGANG SAHAM (RUPS) DALAM PERSEROAN TERBATAS - Rasheldy Putri Adiwinata; Putra Hutomo; Yuliana Setiadi (Journal of Innovation Research and Knowledge, 2025)
Based on Article 1 number 1 of Law Number 40 of 2007 concerning Limited Liability Companies, shares are part of the company's authorized capital where the founders of the company who deposit capital into the company's cash when the PT was first established can also be referred to as shareholders. As a business entity that has legal status, a limited liability company has organs that play a role in carrying out activities in law, one of which is the GMS. The GMS is a forum consisting of the company's shareholders, where the GMS acts as a liaison between the majority and minority shareholders with the company, but in practice many decisions taken by the majority in the GMS are considered not always fair to minority shareholders so that the interests of the minority are less considered. such as case examples In the decision of case number 217 PK/Pdt/2014, the decision of the high court number 477/PDT/2017/PT.BDG and the case study of PT INDOSAT TBK and PT H 3 I. The formulation of the problem in this study is how the legal consequences of not including minority shareholders in the implementation of the GMS and legal protection for minority shareholders in the implementation of the GMS. The legal theory used in this study is the theory of legal consequences and the theory of legal protection.The method used in this study is a normative legal research type, namely legal research conducted by examining library materials or secondary data only. The research approaches used are the Statutory Approach, Conceptual Approach, Analytical Approach, Case Approach and Data collection techniques are carried out by identifying and inventorying positive legal rules, examining library materials, and other sources of legal materials. For the Legal Material Analysis Technique using grammatical interpretation, historical interpretation, systematic interpretation, and legal construction methods.The results of this study are that the legal consequences of not including shareholders in the GMS are that shareholders can file a derivative lawsuit to the Court as stipulated in Article 61 paragraph (1) of the PT Law. This is in line with R. Soeroso's legal theory, which states that in essence the legal consequences are the impacts caused by an act or legal action on the rights and obligations of the parties and legal protection for minority shareholders is regulated in Article 61 paragraph (1) of the PT Law which in essence emphasizes that shareholders may file a lawsuit, while the lawsuit in question is a derivative lawsuit on the condition that there is a GMS decision that is detrimental to the company, the plaintiff has a minimum of 10% of shares. The suggestion in this study is that minority shareholders at the time of the establishment of the company should pay attention to matters relating to the company's finances included in the Articles of Association so that minority shareholders have a legal basis and to the Government to make government regulations relating to legal protection for minority shareholders, namely regulations regarding the formation of a special dispute council regulating Limited Liability Companies.